The impact of work ethic and performance allowances on employee performance by moderating work motivation in BAPPEDA Provinsi Jawa Timur - Andansari, Silvy Eka; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to determine the impact of work ethic and performance allowances on employee performance by moderating work motivation in BAPPEDA Provinsi Jawa Timur. This research uses an approach with quantitative methods. Data collection was obtained from the distribution of questionnaires. The data obtained were analyzed through the SEM PLS method and bootstrapping using Smart PLS software Version 4.0. The respondents in this study were 49 employees from 97 BAPPEDA Provinsi Jawa Timur employees. Using the Likert scale, the data collection instrument uses variables of work ethic, performance benefits, work motivation, and employee performance. The study showed that work ethic and performance benefits positively and significantly affected employee performance. In contrast, work motivation has an insignificant effect on employee performance. Moderation of work motivation strongly influences work ethic and employee performance. Meanwhile, moderation of work motivation does not affect performance allowances on employee performance.